Intercellular diffusion of cyclic nucleotides followed by gap junction closure restarts meiosis in mouse preovulatory follicles - Iris F. Nakashima; Haining Zhong; Viacheslav O. Nikolaev; Corie M. Owen; Siu-Pok Yee; Laurinda A. Jaffe; Jeremy R. Egbert (Proceedings of the National Academy of Sciences, 2025)
Signaling by luteinizing hormone (LH) in the outer granulosa cells of mammalian ovarian follicles causes meiosis to resume in the oocyte, located ~10 cell layers away, preparing the oocyte for ovulation and fertilization. This long-distance communication is accomplished by cAMP and cGMP diffusion through gap junctions, but knowledge of cAMP dynamics in the oocyte is based on static measurements, and information about cAMP changes in the granulosa cells has not been integrated with information about cAMP changes in the oocyte. By simultaneous multihour imaging of both compartments of live ovarian follicles, using mice expressing an improved cAMP sensor, we elucidate how the meiosis-activating signal is transmitted. In response to LH, cAMP generated in the granulosa cells diffuses within ~10 min to the oocyte. cAMP in the granulosa cells then remains high for at least 5 h, but over a 3-h period, cAMP in the oocyte decreases to a new plateau level below the original baseline. We show that the cAMP decrease in the oocyte depends not only on the established mechanism of LH lowering cGMP in the oocyte, which relieves inhibition of the PDE3A phosphodiesterase in the oocyte, but also on the subsequent LH-induced closure of gap junctions between the granulosa cells. This closure prevents cAMP from diffusing into the oocyte from the granulosa cells, a concept that has been proposed but not previously tested. We conclude that LH coordinates changes in both cGMP and gap junctions to lower cAMP in the oocyte, reinitiating meiotic progression.